2002
DOI: 10.1111/j.1572-0241.2002.05831.x
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Psychomotor Responses After Conscious Sedation in Cirrhotic Patients Undergoing Therapeutic Upper Gi Endoscopy

Abstract: A total of 61 consecutive cirrhotic patients who underwent therapeutic upper GI endoscopy completed the study. The mean presedation NCT time was 43.5 s (95% CI = 39.0-48.1 s) and the mean postsedation NCT time 60.0 s (95% CI = 50.7-69.3 s). The difference between the mean pre- and postsedation NCT times was 16.4 s (95% CI = 9.8-23.1 s; p < 0.001). A total of 38 consecutive patients without clinical or biochemical evidence of liver disease who presented for upper GI endoscopy completed the NCT as described for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
1
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 18 publications
6
32
1
8
Order By: Relevance
“…5,9,11,[16][17][18][19] Nevertheless, caution is advised when sedation with benzodiazepines and opioids is administered in patients with liver disease. Hepatic flow is one of the main factors involved in metabolism and elimination of midazolam.…”
Section: Discussionmentioning
confidence: 99%
“…5,9,11,[16][17][18][19] Nevertheless, caution is advised when sedation with benzodiazepines and opioids is administered in patients with liver disease. Hepatic flow is one of the main factors involved in metabolism and elimination of midazolam.…”
Section: Discussionmentioning
confidence: 99%
“…Recovery from sedation varies significantly, depending on the drug used, and, although alertness can be recovered quickly and the patient may be fit for discharge after sedation with a benzodiazepine plus an opioid, neuromotor function is often impaired, and most international recommendations regarding the recovery of patients from sedated endoscopy ban the patient from active participation in traffic for 24 hours. [1][2][3][4][5] Our study demonstrated that residual effects of midazolam after EGD affected various aspects of psychomotor function for at least 2 hours after the injection. 8 The average recovery time after colonoscopy also was much longer for patients receiving a combination of a benzodiazepine and a narcotic (54.9 minutes) than for patients receiving propofol alone (15.6 minutes).…”
Section: Discussionmentioning
confidence: 99%
“…Les patients d'âge avancé et les patients présentant une pathologie coronarienne ou pulmonaire avaient un risque augmenté de complications cardiorespiratoires liées à une sédation pour une endoscopie digestive [51,52].…”
Section: âGe Du Patientunclassified
“…Les patients cirrhotiques sédatés par benzodiazépine présentaient fréquemment des encéphalopathies postendoscopies [52].…”
Section: Cirrhoseunclassified
See 1 more Smart Citation